Effective Local Leadership as an Instrument and Model in Stunting Handling in Mongpok Village Serang Regency - Sururi, Ahmad; Ungku Mohd Nurdin, Ungku Khairunnisa bt; Sartika Iriany, Ieke; Pasciana, Rostiena (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
Stunting is a significant health issue in most countries around the world, and various research evidence from different countries has shown that most of the success in tackling stunting is due to effective local leadership. This study aims to discuss effective local leadership in addressing stunting in Mongpok Village, Serang Regency, Banten Province, Indonesia, using four concepts or dimensions of leadership, namely transformational leadership, collaborative leadership, socio-cultural leadership, and shared leadership, as well as formulating an effective local leadership model. The research used a qualitative descriptive approach through data collection techniques through interviews and observations. The data were analyzed using systematic qualitative data analysis through classification (coding), labeling, category preparation, and data classification. The research results show that the four dimensions of leadership, namely transformational, collaborative, sociocultural, and shared leadership, contribute and complement each other in encouraging the success of effective local leadership in dealing with stunting. The research findings show the importance of responsive leadership, collaborative leadership based on planning and openness, leadership oriented to local wisdom, leadership that positions the community as the leading actor, and effective local leadership model in handling stunting. This research concludes that effective local leadership is evidence of successful stunting handling in Mongpok Village, Indonesia.